LncRNA MEG8 promotes NSCLC progression by modulating the miR-15a-5p-miR-15b-5p/PSAT1 axis - Guo, Kai (Cancer Cell Int, 2021)
BACKGROUND: Non-small cell lung cancer (NSCLC) is the most common tumor with severe morbidity and high mortality. Long non-coding RNAs (lncRNAs) as crucial regulators participate in multiple cancer progressions. However, the role of lncRNA MEG8 in the development of NSCLC remains unclear. Here, we aimed to investigate the effect of lncRNA MEG8 on the progression of NSCLC and the underlying mechanism. METHODS: Cell proliferation was analyzed by EdU assays. The impacts of lncRNA MEG8, miR-15a-5p, and miR-15b-5p on cell invasion and migration of NSCLC were assessed by transwell assay. The luciferase reporter gene assay was performed using the Dual-luciferase Reporter Assay System. The effect of lncRNA MEG8, miR-15a-5p, and miR-15b-5p on tumor growth was evaluated in nude mice of Balb/c in vivo. RESULTS: We revealed that the expression levels of MEG8 were elevated in the NSCLC patient tissues compared to that in adjacent normal tissues. The expression of MEG8 was negatively relative to that of miR-15a-5p and miR-15b-5p in the NSCLC patient tissues. The expression of MEG8 was upregulated, while miR-15a-5p and miR-15b-5p were downregulated in NSCLC cell lines. The depletion of MEG8 inhibited NSCLC cell proliferation, migration, and invasion in vitro. MEG8 contributed to NSCLC progression by targeting miR-15a-5p/miR-15b-5p in vitro. LncRNA MEG8 contributes to tumor growth of NSCLC via the miR-15a/b-5p/PSAT1 axis in vivo. Thus, we concluded that lncRNA MEG8 promotes NSCLC progression by modulating the miR-15a/b-5p/PSAT1 axis. CONCLUSIONS: Our findings demonstrated that lncRNA MEG8 plays a critical role in NSCLC development. LncRNA MEG8, miR-15a-5p, miR-15b-5p, and PSAT1 may serve as potential targets for NSCLC therapy.